Integrated information system via wifi technology / Ng Yin Chern - Ng , Yin Chern (2003)
In the future work space, the ability to make decision based on live and updated data is ultimately important. The key motivation of this project therefore to enable and enhance data mobility. Wireless LAN (WiFi) application is becoming more popular and there are a growing number of WiFi hotspots around the country. This makes it feasible and suitable for the project to utilize the Wifi technology as tis core concept. Also, portable devices such as the PocketPC’s are now powerful enough for a full blown application. The project namely the integrated information system via WiFi technology sought to solve are enhancing data mobility and also enhance data integration by utilizing both the groundbreaking and new WiFi and PDA technologies. The outcome of the is project is to create a fully synchronize-able information system environment using wireless technology, updating information and schedules to the users of this system even when they are on the move securely via strong security encryption which is DES/TDES. A very modular approach in the development of the project is being taken by being modular, the codes could cosily be reusable throughout the system. This would easily solve the important issues of data integration. This project would try to solve this by being able to utilize and connect to different types of database. This could be done as the development of the project is very modular. Therefore, the groundbreaking NET Framework is the main development tool that would be used in the development of this project. Also, MS SQL Server 2000, MS Access and lastly database would be used depending on the different platforms in the systems.